Efektivitas Penggunaan Video Pembelajaran dalam Meningkatkan Pemahaman Pendidikan Agama Islam di Era Digitalisasi Siswa Kelas 3 SDN 011 Bontang Selatan Tahun Pelajaran 2023/2024 - Anisa, Alya Nur; Ihsan, Muh. (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research aim to discusses the effectiveness of using instructional videos to improve the quality of Islamic Religious Education (PAI) learning for third-grade students at SDN 011 Bontang Selatan. It examines how effective the use of instructional videos is in enhancing the understanding of Islamic Religious Education in the digital era for students at SDN 011 Bontang Selatan. The background of this research revolves around the learning system using instructional videos to enhance the understanding of PAI. The purpose of this study is to determine whether the effectiveness of using instructional videos can improve the understanding of Islamic Religious Education in the digital era and how the understanding of Islamic Religious Education among students at SDN 011 Bontang Selatan has improved using instructional videos in the digital era during the 2023/2024 academic year compared to before the use of instructional videos. This research is qualitative in nature. Data collection techniques used include observation, interviews, and documentation. Data analysis techniques employed are data reduction, data presentation, and conclusion drawing. The results of the research on the effectiveness of using instructional videos in improving the understanding of Islamic Religious Education in the digital era among third-grade students at SDN 011 Bontang Selatan, using data reviews through interviews, observations, and documents conducted both directly and online, indicate that digital-based learning greatly aids the learning process and plays a significant role in building students' learning motivation. The conclusion from this research is that the use of instructional videos has proven effective in enhancing students' understanding of Islamic Religious Education in the digital era. This is evident from the significant improvement in their understanding of Islamic Religious Education compared to traditional teaching methods previously used.